Economic policy uncertainty and enterprise export resilience in China: Does the digital economy matter? - Xiugang Zhu; Yunxin Ye (Heliyon, 2024)
In the new era of international trade, escalating uncertainty and the swift development of the digital economy stand out as two pivotal transformations. These phenomena individually exert significant influences on enterprises' exports; however, their combined effects on export resilience remain underexplored. Hence, drawing on existing theories, this paper analyzes the weakening effect of economic policy uncertainty on export resilience and explores the influence of regional digital economic development on this attenuation effect. Furthermore, empirical tests are conducted using micro-level data from China. The study findings reveal: (1) Economic policy uncertainty weakens firms' export resilience by increasing transaction costs; (2) Digital economic development mitigates this weakening effect by reducing transaction costs, with a more pronounced effect observed among highly efficient firms. The findings suggest that amid escalating uncertainty, vigorously promoting digital economic development holds profound policy significance for the high-quality development of international trade.